A microbial carbon-phosphorus bond cleavage enzyme requires two protein components for activity. - Murata, K (1989)
Enterobacter aerogenes IFO 12010 contains a carbon-phosphorus (C-P) bond cleavage enzyme catalyzing the liberation of inorganic phosphate from various alkyl- and phenylphosphonic acids. The enzyme in the bacterium was found to be composed of two physically different protein components, E2 and E3. The molecular weights of E2 and E3 were 560,000 and 110,000, respectively, and E3 was resolved into two apparently homogeneous subunits. Neither component alone could catalyze the C-P bond cleavage reaction, but the reaction was efficiently catalyzed when the components were mixed.